2016
DOI: 10.1007/s00268-016-3491-4
|View full text |Cite
|
Sign up to set email alerts
|

The C‐reactive Protein to Albumin Ratio Predicts Long‐Term Outcomes in Patients with Pancreatic Cancer After Pancreatic Resection

Abstract: The CRP/Alb ratio may be an independent and significant indicator of poor long-term outcomes in patients with pancreatic cancer after pancreatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 35 publications
1
116
0
1
Order By: Relevance
“…The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41). Subsequently, multiple studies have demonstrated that the CRP/Alb ratio exhibited prognostic value in numerous types of cancer (15)(16)(17)(18)42). The present study revealed that a high CRP/Alb ratio indicated increased tumor invasion and metastasis and poorer prognosis compared with a low CRP/Alb ratio.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41). Subsequently, multiple studies have demonstrated that the CRP/Alb ratio exhibited prognostic value in numerous types of cancer (15)(16)(17)(18)42). The present study revealed that a high CRP/Alb ratio indicated increased tumor invasion and metastasis and poorer prognosis compared with a low CRP/Alb ratio.…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study, Alb was used to estimate nutritional status. For patients with GC, protein digestion and absorption were decreased, whereas protein metabolism was increased, resulting in a negative nitrogen balance (18,39). The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, CAR is novel. Haruki et al [19] suggested that for pancreatic cancer patients after pancreatic resection, CAR could be an independent and significant indicator of poor long-term outcome. Shibutani et al [21] found preoperative CAR to be a useful prognostic marker in patients with colorectal cancer undergoing potentially curative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP/ALB ratio was originally developed by Fairclough et al to predict the patient outcome 14. The CRP/ALB ratio has been identified as an independent prognostic factor in several malignancies, including hepatocellular carcinoma 11, esophageal cancer 12, pancreatic cancer 18 and small cell lung cancer 19. Furthermore, Ranzani et al revealed the CRP/ALB ratio was more accurate than CRP level alone for predicting mortality in patients with sepsis 14.…”
Section: Discussionmentioning
confidence: 99%